Prevalence of Hyperuricemia and Its Risk Factors Among Residents of a Rural Field Practice Area in Belagavi, India - Muthusamy, Sasitharan; Kulkarni, Rajesh R; Khot, Poornima B (National Journal of Community Medicine, 2024)
Background: Serum Uric Acid (SUA) is often overlooked in primary healthcare, primarily associated with Gouty Arthritis. However, the literature indicates its links to dyslipidaemia, cardiovascular diseases, hypertension, and metabolic syndrome. This study aimed to determine the prevalence of hyperuricemia and its associated risk factors among rural residents. Methodology: A cross-sectional study was conducted from January to May 2023, involving 300 individuals aged ≥30 during routine NCD screening. Data on socio-demographics, meat consumption habits, thiazide diuretic usage, and anthropometric measurements were collected. Blood samples were obtained for SUA analysis after informed consent. Results: Participants had a median age of 45 years, BMI of 25.41 kg/m², and SUA level of 5 mg/dl. The study revealed an overall hyperuricemia prevalence of 32.7%. While no significant associations were found between hyperuricemia and the variables analysed, a statistically significant positive linear correlation emerged between SUA levels and waist or hip circumference. Binary logistic regression showed a significant association between hyperuricemia and the frequency of meat consumption. Conclusion: This study suggests that SUA can serve as a valuable tool in primary healthcare. Identifying and treating individuals with hyperuricemia, and educating those at risk, can help prevent future vascular events.